Campur Kode dalam Proses Pembelajaran di Sekolah Dasar Negeri 12 Padang Laweh Kabupaten Sijunjung - Ratna Syafitri Yanti; Afrini Rahmi; Ria Satini (AIJER: Algazali International Journal Of Educational Research, 2023)
Abstract: Code Mixing in the Learning Process at Padang Laweh 12 Public Elementary School, Sijunjung Regency. The purpose of this study is to describe the forms and factors that cause code mixing in the learning process at Padang Laweh 12 Public Elementary School, Sijunjung Regency. This type of research is qualitative research. The research method uses descriptive method. The data in this study are words, phrases, clauses in the learning process at Padang Laweh 12 Public Elementary School, Sijunjung Regency. The sources in this study are audio and video recordings in the process. The results of the research that has been done, found 86 code mixing data in the learning process at Padang Laweh 12 Public Elementary School, Sijunjung Regency. Of the 86 data found, there were 35 mixed code words such as no, okay, uwang, kecek, rest, reminded, ado, there, etc., 32 mixed code phrases such as alhamdulillah, allhu akbar, what did you check mom earlier?, bakpo wak , cubo baco, and others, and 18 code mixing clauses such as ha kambiongmelompek pageg jie serli, how come you can't wak kluag de, and others. In this study, there is also code mixing based on its nature, namely internal (internal) code mixing such as Indonesian to Minangkabau and vice versa and external (external) code mixing such as Indonesian to Arabic and vice versa. The causes of code-mixing are the speaker or speaker's personal factors, function and purpose factors, and the factor of arousing a sense of humor with jokes (funny impression).